Effect of Weed Management Practices on Growth, Yield, and Profitability of Hybrid Maize at Dang, Nepal - Paudel, Santosh; Neupane, Madhav Prasad; Poudel, Dikshya (Agronomy Journal of Nepal, 2025)
Weeds pose a major challenge in maize cultivation, resulting in financial losses for farmers and becoming a major burden. To achieve financial sustainability for hybrid maize growers, understanding the effect of weeds on growth, yield, and profitability is important. We examined the effect of various weed management practices on the growth, yield, weed dynamics, and profitability of hybrid maize in Dang, Nepal. Organized in a Randomized Complete Block Design (RCBD) with four replications, our experiment included five treatments: atrazine at the rate of 1 kg a.i. ha-1, two-hand weeding at the rate of 20 and 40 DAS, black on silver plastic mulching, power weeder at the rate of 20 and 40 DAS, and a weedy check. The results revealed that treatment black-on-silver plastic mulching led to the highest grain yield (9.91 t ha-1), significantly outperforming the atrazine treatment, two-hand weeding, power weeder, and weedy check treatments. We found 15 different weed species across six plant families, with broadleaf and grassy weeds predominating over sedge weeds during the initial stages of crop growth. Total weed density and dry weight were lowest with the black-on-silver plastic mulching compared to other treatments. Additionally, black-on-silver plastic mulching resulted in superior weed control efficiency, achieving rates of 96.31%, 95.86%, and 96.20% at 30, 45, and 90 days after sowing (DAS), respectively. Atrazine application proved to be the most profitable, resulting in the highest net return and benefit-cost ratio. The results showed that while black-on-silver plastic mulching significantly enhances the grain yield of hybrid maize by effectively suppressing weed growth, atrazine application emerges as the most economically viable weed management practice.